Prevalence and trends of transfusion transmissible infections among blood donors in the State of Qatar, 2013–2017 - Mohamed Aabdien; Nagah Selim; Sayed Himatt; Saloua Hmissi; Zeyd Merenkov; Noora AlKubaisi; Manar E. Abdel-Rahman; Abdelatif Abdelmola; Shadi Khelfa; Elmoubasher Farag; Hamad E. Al-Romaihi; Mohamed Al-Thani; et al. (BMC Infectious Diseases, 2020)
Abstract Background Millions of lives around the world are being saved annually through blood transfusion. However, blood transfusion is among the essential vehicles for transmitting infections. The overall prevalence of Transfusion Transmissible Infections among blood donors differs around the world, reflecting the variation in the prevalence of these infections. This study aims to assess the prevalence and trends of Transfusion Transmissible Infections among blood donors in Qatar. Methods This is a cross-sectional study utilizing donation records of 5 years from January 2013 to December 2017. We included in the study results for all screening and confirmatory tests for Hepatitis B Virus, Hepatitis C Virus, Human T-lymphotropic Virus-I/II, Syphilis and Malaria. Results Among the 190,509 donations received at the donation centre during the study period, about 91% of donations were received from males and 9% from females. The overall positivity rate for all tests was 1.87, 2.23, 1.78, 2.31, 2.67% for the years 2013 through 2017, with an increasing yearly trend by 6% each year. The overall positivity rates for Hepatitis C Virus, Human T-lymphotropic Virus-I/II, Hepatitis B Virus, Syphilis and Malaria (2013–2017) were 0.60, 0.18, 0.30, 0.43 and 0.20%, respectively. Conclusion The overall positivity rate of all tests combined for the Transfusion Transmissible Infections demonstrated a gradually increasing trend from 2013 to 2017. However, the trend for each infection (Hepatitis C Virus, Hepatitis B Virus, Syphilis and Malaria) was fluctuating except for Human T-lymphotropic Virus-I/II, which was increasing. Supporting the development of effective prevention and control strategies requires further comprehensive investigations for better estimation of the burden of these infections.